Peran Produser dalam Pembuatan Video Feature “Merajut Asa Sepatu Lokal di Era Digital” - Muhammad Faishal Arkan Pranata; Efi Fadilah; Nurmaya Prahatmaja (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The role of a producer in video feature production is central. This report aims to examine the management of the production prosess by the producer, starting from the pre production, production, and post production stages to ensure that the branding massage is optimally delivered to the target audience. The producer is not only in charge of formulating the concept and coordinating the production team, but also has the main responsibility in harmonizing the creative and technical aspects to produce an interesting and relevant video. The digital distribution strategy through the TikTok social media platform is a breakthrough in branding MSMEs amidst increasingly fierce competition with outside industries. The effectiveness of producer’s role in video feature production depends not only on managerial skills, but also on understanding digital trends and consumer behaviour, so as to create content that has maximum appeal and impact in building the MSME brand.